Antibacterial test of red ginger (Zingiber officinale var. rubrum) extracts at 10%, 30% and 60% on the growth of Streptococcus mutans: Uji antibakteri ekstrak jahe merah (Zingiber officinale var. rubrum) 10%, 30%, dan 60% terhadap pertumbuhan Streptococcus mutans - I Gusti Agung Ayu Hartini; I Gusti Ngurah Bagus Tista; Ni Made Bella Fransiska Anggraini (Makassar Dental Journal, 2026)
Red ginger rhizome (Zingiber officinale var. rubrum) is a plant that is often used as a research material and contains antibacterial compounds such as flavo-noids, oleoresin, essential oils and tannins. This study explored the use of RG extract to inhibit the growth of Streptococcus mutans through laboratory experi-ments using a post-test only control group design, with 24 samples consisting of a positive control group treated with vancomycin antibiotics, and groups trea-ted with RG extract at concentrations of 10%, 30% and 60%. The inhibition power at a concentration of 10% was 6.5 mm, 30% was 6.83 mm, and 60% was 8.83 mm. The higher the extract concentration, the greater the amount of antibacterial compounds released. It was concluded that the inhibition power of RG extract concentrations of 10%, 30% and 60% could inhibit the growth of S.mutans; the 60% concentration was the most effective.